Evaluation of IR Biotyper for carbapenem-resistant Pseudomonas aeruginosa typing and its application potential for the investigation of nosocomial infection - Hu, Yanyan; Zhu, Kun; Jin, Dingping; Shen, Weiyi; Liu, Congcong; Zhou, Hongwei; Zhang, Rong (Frontiers in Microbiology, 2023)
P. aeruginosa is one of the most common opportunistic pathogens causing severe nosocomial infections for its patterns of multidrug resistance, particularly for carbapenems. Timely epidemiological surveillance could greatly facilitate infection control of P. aeruginosa and many deadly pathogens alike. IR Biotyper (IRBT), is a novel real-time typing tool, based on a Fourier-transform infrared (FTIR) spectroscopy system. It is critical to comprehensively establish and evaluate the feasibility of IRBT in P. aeruginosa strain typing. In the current study, we first established standards and schemes for its routine laboratory application, and we found that Mueller–Hinton agar plates give better discriminatory power than blood agar plates. Data showed that the cut-off value of 0.15 with an additional 0.025 range was optimal. Secondly, twenty-seven clinically isolated carbapenem-resistant P. aeruginosa (CRPA) strains collected from October 2010 to September 2011 were evaluated for typing effectiveness by comparing IRBT to the other commonly used typing methods, such as multi-locus sequence typing (MLST), pulsed-field gel electrophoresis (PFGE) and whole-genome sequencing (WGS)-based typing. When using WGS-based typing as the reference method, the typing method of FTIR spectroscopy (AR=0.757, SID=0.749) could better cluster P. aeruginosa strains than MLST and in silico serotyping (AR=0.544, SID=0.470). Though PFGE showed the highest discriminatory power, low concordance was observed between PFGE and the other methods. Above all, this study demonstrates the utility of the IRBT as a quick, low-cost, real-time typing tool for the detection of CRPA strains.